UV-triggered dopamine polymerization: control of polymerization, surface coating, and photopatterning - Du, Xin; Frenkel, Nataliya; Grunze, Michael; Levkin, Pavel (Advanced materials, 2014)
UV irradiation is demonstrated to initiate dopamine polymerization and deposition on different surfaces under both acidic and basic pH. The observed acceleration of the dopamine polymerization is explained by the UV-induced formation of reactive oxygen species that trigger dopamine polymerization. The UV-induced dopamine polymerization leads to a better control over polydopamine deposition and formation of functional polydopamine micropatterns.